درجة القلق الامتحان لدى طلبة الخامس الإعدادي في أداء الاختبار (الامتحان) - كاظم, صبري عبدالله (lark, 2018)
The aim of the research was to identify the degree of psychological anxiety among the students of the fifth year in the performance of the exam. The research sample consisted of 150 students with 75 students and 75 students from the fifth grade preparatory school in Dhi Qar Governorate Education Department In order to achieve the objectives of the research, the researcher adopted the measure of anxiety (Abu Arab, 1994). This measure was chosen without jealousy because its paragraphs cover all forms and types of exam anxiety consisting of (52) The validity and consistency of the scale were verified and the statistical analysis package (SPSS) was adopted for use Production results showed the results: